Le cinéma américain : un impérialisme culturel ? - Nathalie Dupont (Revue LISA)
There are many people who equate American cinema with the domination of world screens. It is not a new trend and it is true that the American studios have always tried to have the biggest market share in all the countries showing their films. Yet, the paradox is that those countries can take advantage of the American presence on their soil; for example, taxation of profits or of ticket sales can finance local productions while the various American “runaway productions” enable some countries to develop or update their own cinematographic infrastructures and at the same time provide the opportunity for their local technicians to improve their skills. It is thus possible to take advantage of the American domination that is predominantly an economic one and that follows the trend of globalisation.